Hardfacing behavior of Cr-Ni stainless steel with Co-based super alloys - Nursoy, Mustafa; Yaz, Mehmet; Celik, Halis (Carl Hanser Verlag, 2008)
In this study, the hardfacing behavior of Cr-Ni stainless steel was studied by depositing of Stellite 1, Stellite 6, and Stellite 12 superalloys on Cr-Ni stainless steel specimens using electric arc welding and tungsten inert gas welding. The cobalt base alloys were hardfaced on stainless steel plates as a single layer. The samples taken from the hardfaced materials were studied by optical microscopy, scanning electron microscopy, X-ray diffraction, and micro-hardness measurements. The hardness and wear resistance values of the layer obtained after the hardfacing processes are satisfactory and the process seem to be suitable for application.
Keywords: Hardfacing; Stellites; Cr-Ni stainless steels